Rediscovery of two endemic species of Berberis from Uttarakhand, Western Himalaya, India - Tiwari, Umeshkumar L.; Rawat, Gopal Singh; Adhikari, Bhupendra Singh (Biodiversity: Research and Conservation, 2013)
Two endemic Berberis species (Berberidaceae) viz., Berberis ahrendtii R. R. Rao and Uniyal and Berberis lambertii Parker, are first time rediscovered after ca. 100 years since their type localities were found. These species are recorded from the Chamoli and Pithoragarh districts of Uttarakhand, India. Taxonomic description, synonyms, distribution information, locality details of specimens examined and photographs are provided for each species.